Psychosocial Factors Contributing to Suicidal Ideation in Hospitalized Schizophrenia Patients in Korea - Kim, Sung-Wan; Kim, Su-Jung; Mun, Ji-Woong; Bae, Kyung-Yeol; Kim, Jae-Min; Kim, Seon-Young; Yang, Su-Jin; Shin, Il-Seon; Yoon, Jin-Sang (Psychiatry investigation, 2010)
This study aimed to comprehensively evaluate psychosocial risk factors associated with suicidality in patients with schizophrenia in Korea. The study sample consisted of 84 hospitalized patients with schizophrenia. Suicidal thoughts and a clear desire to be dead within 2 weeks were defined as a current suicidal ideation. Socio-demographic and clinical variables, including family history of completed suicides and psychiatric illnesses, were collected, and the Positive and Negative Syndrome Scale (PANSS), Calgary Depression Scale for Schizophrenia (CDSS), Beck Depression Inventory (BDI), Simpson-Angus Scale (SAS), Scale to assess Unawareness of Mental Disorder (SUMD), and Alcohol Use Disorders Identification Test (AUDIT) were administered to identify factors associated with a current suicidal ideation. Forty-three subjects (51.2%) reported clear suicidal ideation. Multivariate analysis revealed that later age of illness onset, previous suicide attempt, family history of completed suicide, depression, or substance abuse, fewer than one family visitation to the hospital per month, and score on the CDSS were independently related to current suicidal ideation in these subjects. Age, education level, and scores on the SUMD were not significantly associated with current suicidal ideation in the multivariate analysis, but were associated with suicidal ideation in a univariate analysis on the level of p<0.1. The above clinical factors should be evaluated to predict and prevent suicidal risk in patients with schizophrenia. In particular, modifiable factors such as depression should be managed to reduce suicidality of hospitalized patients with schizophrenia.